Silica sol composition, chemical mechanical polishing composition, and polishing method
Patent Information
- Application Number
- CN202610860863.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-15
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-06-15
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the field of chemical mechanical polishing technology, and more particularly to a silica sol composition, a chemical mechanical polishing composition, and a polishing method. Background Technology
[0002] As large-scale integration (LSI) advances towards higher integration and performance, semiconductor manufacturing processes face increasingly stringent requirements. This necessitates the use of more layers and denser metal wiring (i.e., high-precision multilayer stacked structures) to achieve finer pattern layouts. LSI devices consist of a multilayered three-dimensional structure formed by the alternating deposition of various functional thin films, including insulating layers, barrier layers, gate layers, electrode layers, and wiring layers. This structure demands extremely high levels of uniformity in layer thickness, surface flatness, and interlayer alignment accuracy, making it a core structural form for realizing high-density, high-performance advanced semiconductor devices. In the manufacturing process of these semiconductor devices, chemical mechanical polishing (CMP) technology can achieve nanometer-level high flatness, effectively avoiding the decline in production yield caused by the accumulation of manufacturing processes, and is one of the key processes in semiconductor manufacturing.
[0003] In the fabrication of memory and logic chips, silicon dioxide (OX) is a commonly used dielectric layer material, while silicon nitride (SiN) is mostly used as an etch stop layer. In LSI manufacturing processes, multiple functional thin films, such as silicon nitride stop layers, silicon dioxide dielectric layers, and polysilicon gate or electrode layers, are deposited alternately to form a multilayer three-dimensional device structure. The silicon dioxide dielectric layer and silicon nitride stop layer need to be polished to meet the flatness requirements of subsequent processes. It has extremely high requirements for interlayer thickness uniformity, global surface flatness, and interlayer alignment accuracy, making it a key structural form for realizing high-density, high-performance advanced semiconductor devices.
[0004] This places stringent demands on the precision control of the polishing system. On one hand, the polishing rate ratio of silicon nitride to silicon dioxide must be strictly controlled to achieve a 1:1 ratio to ensure simultaneous and uniform removal of both layers. This avoids uneven film thickness or localized over-polishing due to differences in polishing rates, which could lead to dishing and erosion. This ensures the high-precision, multi-layered stacked structure meets the stringent surface morphology requirements and guarantees the focusing and interlayer alignment accuracy of subsequent photolithography processes. On the other hand, since the polysilicon gate is a critical functional layer, its thickness and morphology must be strictly controlled. The height of the polysilicon gate directly relates to the chip's threshold voltage and driving performance. Therefore, the polishing rate of the polysilicon must be significantly suppressed to prevent excessive reduction of the gate height during polishing. Ultimately, this ensures precise acquisition of the target film thickness and the preset gate height, guaranteeing that the chip's electrical performance meets design specifications.
[0005] Therefore, developing a chemical mechanical polishing composition that simultaneously satisfies the 1:1 grinding rate selection ratio of silicon nitride and silicon dioxide and effectively suppresses the grinding rate of polycrystalline silicon films has become an urgent need in the current semiconductor manufacturing field. Summary of the Invention
[0006] This application provides a silica sol composition, a chemical mechanical polishing composition, and a polishing method. By making the polishing rate selection ratio of silicon nitride to silicon dioxide approximately 1:1, a highly uniform global planarization of the wafer surface is achieved, which meets the stringent requirements of high-precision multilayer stacked structures for surface morphology. At the same time, the polishing rate of polysilicon is suppressed, protecting key structures such as gates and electrodes from damage, and adapting to advanced LSI manufacturing processes.
[0007] In a first aspect, this application provides a silica sol composition comprising:
[0008] Colloidal silica particles, wherein the colloidal silica particles are anion-modified, and the content of the colloidal silica particles is 5-20 wt%.
[0009] A silicon nitride polishing accelerator, wherein the silicon nitride polishing accelerator is an α,β-unsaturated organic acid compound, and the content of the silicon nitride polishing accelerator is 0.01~0.1wt%;
[0010] A polycrystalline silicon polishing inhibitor, wherein a 1 wt% aqueous solution of the polycrystalline silicon polishing inhibitor has a contact angle of 60~75° on a polycrystalline silicon wafer cleaned with HF at room temperature, and the content of the polycrystalline silicon polishing inhibitor is 0.01~1 wt%.
[0011] The pH value of the chemical mechanical polishing composition is 4-6.
[0012] Secondly, this application provides a chemical mechanical polishing composition, comprising:
[0013] Colloidal silica particles, wherein the colloidal silica particles are anion-modified, and the content of the colloidal silica particles is 5-20 wt%.
[0014] A silicon nitride polishing accelerator, wherein the silicon nitride polishing accelerator is an α,β-unsaturated organic acid compound, and the content of the silicon nitride polishing accelerator is 0.01~0.1wt%;
[0015] A polycrystalline silicon polishing inhibitor, wherein a 1 wt% aqueous solution of the polycrystalline silicon polishing inhibitor has a contact angle of 60~75° on a polycrystalline silicon wafer cleaned with HF at room temperature, and the content of the polycrystalline silicon polishing inhibitor is 0.01~1 wt%.
[0016] The pH value of the chemical mechanical polishing composition is 4-6.
[0017] In one possible implementation, the polycrystalline silicon polishing inhibitor is a high molecular weight polyol, and the average molecular weight of the polycrystalline silicon polishing inhibitor is 400~4000.
[0018] In one possible implementation, the polycrystalline silicon polishing inhibitor is selected from one or more of cellulose compounds, polyalkylene alcohols, and polysaccharide compounds, and the content of the polycrystalline silicon polishing inhibitor is 0.01~0.2wt%.
[0019] In one possible implementation, the polycrystalline silicon abrasion inhibitor is selected from one or more of hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, carboxyethyl cellulose, carboxymethyl cellulose, ethyl hydroxyethyl cellulose, hydroxybutyl methyl cellulose, sodium cellulose sulfate, cellulose phosphate, polyethylene glycol, polypropylene glycol, polybutane glycol, polyhexane glycol, ethylene glycol-propylene glycol block copolymer, ethylene glycol-butane glycol block copolymer, propylene glycol-butane glycol block copolymer, ethylene glycol-propylene glycol random copolymer, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, dextran, chitosan, deacetylated chitosan, carboxymethyl chitosan, hydroxyethyl chitosan, starch, hydroxymethyl starch, hydroxyethyl starch, hydroxypropyl starch, dextrin, maltodextrin, and cyclodextrin. Preferably, the polycrystalline silicon abrasion inhibitor is selected from one or more of hydroxymethyl cellulose, hydroxyethyl cellulose, polypropylene glycol, dextran, and hydroxypropyl cellulose.
[0020] In one possible implementation, the mass ratio of the silicon nitride polishing accelerator to the colloidal silica particles is 1:(500~600).
[0021] In one possible implementation, the silicon nitride polishing accelerator is selected from at least one of α,β-unsaturated carboxylic acids and α,β-unsaturated sulfonic acids, and the silicon nitride polishing accelerator has 2 to 8 carbon atoms.
[0022] In one possible implementation, the silicon nitride polishing accelerator is selected from one or more of acrylic acid, methacrylic acid, ethylacrylic acid, propylacrylic acid, butylacrylic acid, crotonic acid, isocrotonic acid, maleic acid, trans-butenedioic acid, itaconic acid, citraconic acid, mesocarboxylic acid, pentenoic acid, hexenoic acid, heptenic acid, octenic acid, vinyl sulfonic acid, sulfonacrylic acid, methacrylic acid, butenyl sulfonic acid, pentenyl sulfonic acid, hexenyl sulfonic acid, styrene sulfonic acid, maleic acid monosulfonate sulfonic acid, fumaric acid monosulfonate sulfonic acid, and itaconic acid monosulfonate sulfonic acid. Preferably, the silicon nitride polishing accelerator is selected from one or more of vinyl sulfonic acid, sulfonacrylic acid, and styrene sulfonic acid.
[0023] In one possible implementation, the average primary particle size of the colloidal silica particles ranges from 30 to 150 nm, the colloidal silica particles exhibit negative charge in the polishing composition, and the surface zeta potential of the colloidal silica particles is less than -20 mV.
[0024] In one possible implementation, the anion is a carboxylate or sulfonate group, preferably selected from one or more of methanesulfonic acid group and propanesulfonic acid group.
[0025] In one possible implementation, the electrical conductivity of the composition is 0.5~3 mS / cm.
[0026] In one possible embodiment, the composition further includes a conductivity modifier, which is an ammonium salt, and the content of the conductivity modifier is 0.5~3wt%.
[0027] In one possible implementation, the conductivity modifier is selected from one or more of ammonium sulfate, ammonium lactate, ammonium oxalate, ammonium succinate, and ammonium nitrate.
[0028] Thirdly, this application provides a chemical mechanical polishing method, comprising:
[0029] (i) Using a substrate to contact the chemical mechanical polishing composition described in any one of the embodiments of the first aspect above;
[0030] (ii) moving the chemical mechanical polishing composition relative to the substrate; and
[0031] (iii) Grinding away at least a portion of the substrate to polish the substrate;
[0032] The substrate comprises at least one silicon nitride layer and one silicon oxide layer, wherein the ratio of the removal rates of the silicon nitride layer and the silicon oxide layer is 0.95 to 1.10.
[0033] In the above technical solution, by using 5-20 wt% anion-modified colloidal silica particles and 0.01-0.1 wt% α,β-unsaturated organic acid compounds, a polishing rate selection ratio of approximately 1:1 for silicon nitride and silica is achieved. This results in highly uniform global planarization of the wafer surface, meeting the stringent surface morphology requirements of high-precision multilayer stacked structures. Simultaneously, by using 0.01-1 wt% polysilicon polishing inhibitors, excessive reduction in the height of the polysilicon gate during polishing is prevented, protecting critical structures such as the gate and electrodes from damage and maintaining the device's designed thickness and electrical performance stability. Through this synergistic control, process yield and device reliability can be significantly improved, meeting the efficient and stable manufacturing requirements of advanced LSI high-precision multilayer stacked structures. Detailed Implementation
[0034] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0035] It should be noted that the following embodiments are examples of this application and are used only to illustrate this application, and are not intended to limit this application. Other combinations and various modifications within the scope of this application are possible without departing from the spirit or scope of this application.
[0036] The following provides a detailed description of the silica sol composition, chemical mechanical polishing composition, and polishing method provided in this application.
[0037] An embodiment of this application provides a silica sol composition comprising, substantially comprising, or comprising: a liquid carrier, colloidal silica particles, a silicon nitride polishing accelerator, and a polycrystalline silicon polishing inhibitor.
[0038] In this application, the pH value of the silica sol composition is 4 to 6. For example, the pH value of the polishing composition is about 6 or less, about 5.5 or less than 5.5, or about 5 or less than 5. Furthermore, the pH value of the polishing composition is about 4 or greater than 4, about 4.5 or greater than 4.5, or about 5 or greater than 5.
[0039] Any liquid carrier suitable for chemical mechanical polishing can be used in the silica sol compositions of this application. The liquid carrier is typically an aqueous carrier and can be water alone, can include water and a suitable water-miscible solvent, or can be an emulsion. Suitable water-soluble solvents include alcohols, such as methanol, ethanol, etc. Preferably, the aqueous carrier consists of water, more preferably deionized water.
[0040] Colloidal silica particles are anion-modified, with the anions selected from one or more of carboxylate, sulfonate, and phosphate groups. When polishing silica layers, the anion-modified colloidal silica particles can generate strong interactions with the silica surface through hydrogen bonding, significantly improving the polishing rate of silica. Furthermore, anion modification can improve the dispersion stability of colloidal silica particles, reduce scratch defects and particle residue, and improve the surface quality after polishing.
[0041] The content of colloidal silica particles, by weight of the polishing composition, is 5 to 20 wt%, for example, about 5 wt% or more, about 7.5 wt% or more, about 10 wt% or more, or about 12.5 wt% or more. Furthermore, the abrasive particles can be suspended in an aqueous medium with a concentration of about 20 wt% or less, about 17.5 wt% or less, or about 15 wt% or less.
[0042] The silicon nitride polishing accelerator is an α,β-unsaturated organic acid compound. Its strong coordination effect on silicon atoms on the silicon nitride surface promotes the hydrolysis and activation of Si-N bonds, effectively increasing the chemical mechanical polishing rate of silicon nitride. The content of the silicon nitride polishing accelerator, based on the weight of the polishing composition, is 0.01~0.1 wt%; for example, about 0.01 wt% or more, about 0.02 wt% or more, about 0.03 wt% or more, or about 0.05 wt% or more. Furthermore, the content of the silicon nitride polishing accelerator is about 0.1 wt% or less, about 0.08 wt% or less, or about 0.06 wt% or less.
[0043] After cleaning a blank polycrystalline silicon wafer with hydrofluoric acid, a 1 wt% aqueous solution of the polycrystalline silicon polishing inhibitor at room temperature exhibits a contact angle of 60–75° on the polycrystalline silicon wafer. The polycrystalline silicon polishing inhibitor meeting these conditions can form a dense, uniform physically adsorbed film on the polycrystalline silicon surface. This film can shield the active ingredients in the polishing slurry from the direct interaction between the abrasive and the polycrystalline silicon surface, thereby inhibiting the synergistic removal efficiency of chemical etching and mechanical polishing, and reducing the polishing rate.
[0044] The content of the polycrystalline silicon polishing inhibitor, based on the weight of the polishing composition, is 0.01 to 1 wt%; for example, about 0.01 wt% or more, about 0.02 wt% or more, about 0.03 wt% or more, about 0.05 wt% or more, or about 0.08 wt% or more. Furthermore, the content of the polycrystalline silicon polishing inhibitor is about 1 wt% or less, about 0.80 wt% or less, about 0.60 wt% or less, about 0.50 wt% or less, about 0.30 wt% or less, or about 0.20 wt% or less.
[0045] The silica sol composition of this application has a removal rate ratio of 0.95 to 1.10 for silicon nitride and silicon oxide layers, which allows the two dielectric layers to be removed at similar rates. This avoids uneven film thickness or local over-grinding caused by differences in grinding rates, meets the stringent requirements for surface morphology of high-precision multilayer stacked structures, and ensures the accuracy of subsequent photolithography and multilayer processes.
[0046] This application achieves an approximately 1:1 polishing rate selectivity ratio of silicon nitride to silicon dioxide by using 5-20 wt% anion-modified colloidal silica particles and 0.01-0.1 wt% α,β-unsaturated organic acid compounds. This results in highly uniform global planarization of the wafer surface, meeting the stringent surface morphology requirements of high-precision multilayer stacked structures. Simultaneously, the use of 0.01-0.2 wt% polysilicon polishing inhibitors prevents excessive reduction of the polysilicon gate height during polishing, protecting critical structures such as the gate and electrodes from damage and maintaining the device's designed thickness and electrical performance stability. Through this synergistic control, process yield and device reliability can be significantly improved, meeting the efficient and stable manufacturing requirements of advanced LSI high-precision multilayer stacked structures.
[0047] Secondly, this application provides a chemical mechanical polishing composition comprising colloidal silica particles, a silicon nitride polishing accelerator, and a polycrystalline silicon polishing inhibitor. The colloidal silica particles are anionicly modified, and the content of the colloidal silica particles is 5-20 wt%. The silicon nitride polishing accelerator is an α,β-unsaturated organic acid compound, and the content of the silicon nitride polishing accelerator is 0.01-0.1 wt%. A 1 wt% aqueous solution of the polycrystalline silicon polishing inhibitor at room temperature has a contact angle of 60-75° on a polycrystalline silicon wafer cleaned with HF, and the content of the polycrystalline silicon polishing inhibitor is 0.01-1 wt%. The pH value of the chemical mechanical polishing composition is 4-6.
[0048] In this application, the polysilicon polishing inhibitor is a high molecular weight polyol with an average molecular weight of 400-4000. This molecular weight range allows the polyol to form a moderate and uniform adsorption layer on the polysilicon surface, controlling the contact angle between the polysilicon wafer and the polishing slurry within the range of 60-75°. This effectively inhibits mechanical polishing and chemical etching of the polysilicon, achieving a controllable reduction in the polishing rate. Simultaneously, it does not significantly affect the polishing behavior of silicon nitride and silicon dioxide, which is beneficial for improving the polishing efficiency of silicon nitride and silicon dioxide. Furthermore, it maintains a polishing rate selectivity ratio of silicon nitride to silicon dioxide close to 1:1, ensuring the global planarization of the high-precision multilayer stacked structure and protecting the polysilicon functional layers from over-polishing, thinning, or interface damage.
[0049] The polycrystalline silicon abrasion inhibitor is selected from one or more of cellulose compounds, polyalkylene alcohols, and polysaccharide compounds. Examples of cellulose compounds include hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, carboxyethyl cellulose, carboxymethyl cellulose, ethyl hydroxyethyl cellulose, hydroxybutyl methyl cellulose, sodium cellulose sulfate, and cellulose phosphate. Examples of polyalkylene alcohols include polyethylene glycol, polypropylene glycol, polybutanediol, polyhexanediol, ethylene glycol-propylene glycol block copolymers, ethylene glycol-butanediol block copolymers, propylene glycol-butanediol block copolymers, ethylene glycol-propylene glycol random copolymers, and polyethylene oxide-propylene oxide-ethylene oxide triblock copolymers. Examples of polysaccharide compounds include dextran, chitosan, deacetylated chitosan, carboxymethyl chitosan, hydroxyethyl chitosan, starch, hydroxymethyl starch, hydroxyethyl starch, hydroxypropyl starch, dextrin, maltodextrin, and cyclodextrin. Preferably, the content of the polycrystalline silicon polishing inhibitor, based on the weight of the polishing composition, is 0.01 to 0.2 wt%; for example, about 0.01 wt% or more, about 0.02 wt% or more, about 0.03 wt% or more, about 0.05 wt% or more, or about 0.08 wt% or more. Furthermore, the content of the polycrystalline silicon polishing inhibitor is about 0.2 wt% or less, about 0.18 wt% or less, about 0.16 wt% or less, or about 0.12 wt% or less.
[0050] In order to further effectively suppress the grinding of polycrystalline silicon, while improving the grinding efficiency of silicon nitride and silicon dioxide, and maintaining the grinding rate selection ratio of silicon nitride and silicon dioxide close to 1:1, preferably, the polycrystalline silicon grinding inhibitor is one or more selected from hydroxymethyl cellulose, hydroxyethyl cellulose, polypropylene glycol, dextran, and hydroxypropyl cellulose.
[0051] To further control the grinding rate selection ratio of silicon nitride to silicon dioxide to be close to 1:1, in this application, the mass ratio of silicon nitride grinding accelerator to colloidal silicon dioxide particles is 1:(500~600); for example, the mass ratio of silicon nitride grinding accelerator to colloidal silicon dioxide particles is about 1:500, about 1:505, about 1:510, about 1:515, about 1:525, about 1:545, about 1:565, about 1:585, about 1:595, or about 1:600.
[0052] When the mass ratio of silicon nitride polishing accelerator to colloidal silica particles is within the above-mentioned range, it is beneficial to achieve a polishing rate selectivity ratio of silicon nitride to silica of 0.98~1.02, ensuring the global planarization of the high-precision multilayer stacked structure and meeting the stringent requirements of the high-precision multilayer stacked structure for surface morphology. Preferably, the content of colloidal silica particles is 12~20wt%, the content of silicon nitride polishing accelerator is 0.02~0.04wt%, and the mass ratio of silicon nitride polishing accelerator to colloidal silica particles is 1:(500~600).
[0053] To maintain a near 1:1 grinding rate ratio between silicon nitride and silicon dioxide while minimizing surface defects in silicon oxide, the silicon nitride grinding accelerator is selected from at least one of α,β-unsaturated carboxylic acids and α,β-unsaturated sulfonic acids, with a carbon number of 2 to 8. Examples of α,β-unsaturated carboxylic acids include acrylic acid, methacrylic acid, ethylacrylic acid, propylacrylic acid, butylacrylic acid, crotonic acid, isocrotonic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, mesoconic acid, pentenoic acid, hexenoic acid, heptenic acid, and octenic acid. Examples of α,β-unsaturated sulfonic acids include vinyl sulfonic acid, sulfonylacrylic acid, methacrylic acid, butenyl sulfonic acid, pentenyl sulfonic acid, hexenyl sulfonic acid, styrene sulfonic acid, maleic acid monosulfonate sulfonic acid, fumaric acid monosulfonate sulfonic acid, and itaconic acid monosulfonate sulfonic acid.
[0054] To further reduce surface defects in silicon oxide, preferably, the silicon nitride polishing accelerator is selected from one or more of vinyl sulfonic acid, sulfonacrylic acid, and styrene sulfonic acid.
[0055] In this application, the average primary particle size of the colloidal silica particles ranges from 30 to 150 nm. For example, the abrasive particles may have an average particle size of about 30 nm or more, 45 nm or more, 60 nm or more, or 75 nm or more. Furthermore, the abrasive particles may have an average particle size of about 150 nm or less, 130 nm or less, 110 nm or less, or 90 nm or less.
[0056] Colloidal silica particles exhibit negative charge in the polishing composition, with a surface zeta potential of less than -20mV. This negative charge and zeta potential characteristic create strong electrostatic repulsion between the colloidal silica particles, while also generating moderate electrostatic repulsion with the polycrystalline silicon surface. This effectively inhibits excessive abrasion and removal of the polycrystalline silicon film by the abrasive particles, thereby significantly improving the polishing selectivity between silica and polycrystalline silicon. This protects the functional layer of polycrystalline silicon, preventing over-polishing, thinning, and interface damage, and is suitable for the high-precision multilayer stacked structure polishing requirements of LSI processes.
[0057] Preferably, the anion is a sulfonate group, selected from one or more of methanesulfonic acid group and propanesulfonic acid group.
[0058] The silica particles in this application can be colloidal silica prepared by any method, including but not limited to the sodium silicate method and the sol-gel method. From the perspective of reducing the content of metal impurities, colloidal silica prepared by the sol-gel method is preferred. The colloidal silica prepared by this method has a lower content of metal impurities with semiconductor diffusion properties and corrosive ions such as chloride ions, making it more suitable for the field of precision grinding in semiconductors.
[0059] Colloidal silica can be prepared using the sol-gel method, which employs existing known methods. Specifically, hydrolyzable silicon compounds (such as alkoxysilanes and their derivatives) can be used as raw materials and prepared through hydrolysis and condensation reactions.
[0060] Sulfonic acid-based surface modification of colloidal silica can be achieved by: coupling colloidal silica with a silane coupling agent containing thiol groups (e.g., (3-mercaptopropyl)trimethoxysilane), followed by oxidizing the thiol groups with hydrogen peroxide in an aqueous system, thereby covalently bonding sulfonic acid groups to the silica surface.
[0061] Carboxylic acid-based surface modification of colloidal silica can be achieved by: coupling colloidal silica with an alkenyl ester silane coupling agent containing photolytic groups (e.g., (3-(2-nitrobenzyloxycarbonyl)propyl)trimethoxysilane), followed by pyrolysis under ultraviolet light, thereby generating carboxyl groups on the silica surface.
[0062] In this application, the electrical conductivity of the composition is 0.5~3 mS / cm, which facilitates good dispersion stability of the abrasive, improves the grinding efficiency of silicon nitride and silicon dioxide, and allows for a grinding rate selection ratio of silicon nitride to silicon dioxide close to 1:1, meeting the planarization requirements of high-precision multilayer stacked structures. For example, the electrical conductivity of the composition is about 0.5 mS / cm or higher, about 0.8 mS / cm or higher, about 1.0 mS / cm or higher, about 1.2 mS / cm or higher, or about 1.5 mS / cm or higher. Furthermore, the electrical conductivity of the composition is about 3 mS / cm or lower, about 2.75 mS / cm or lower, about 2.5 mS / cm or lower, about 2.25 mS / cm or lower, about 2 mS / cm or lower, or about 1.75 mS / cm or lower. Preferably, the electrical conductivity of the composition is 0.5~2 mS / cm.
[0063] The composition also includes a conductivity modifier, which is an ammonium salt. Examples of ammonium salts include ammonium nitrate, ammonium chloride, ammonium sulfate, ammonium bicarbonate, ammonium carbonate, ammonium acetate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium pyrophosphate, ammonium formate, ammonium citrate, tetraethylammonium chloride, ammonium succinate, ammonium oxalate, ammonium lactate, ammonium malate, and ammonium tartrate. The content of the conductivity modifier is 0.5 to 3 wt%. For example, the content of the conductivity modifier is about 0.5 wt% or higher, about 0.5 wt% or higher, about 0.8 wt% or higher, about 1.0 wt% or higher, about 1.2 wt% or higher, or about 1.5 wt% or higher. Furthermore, the content of the conductivity modifier is about 3 wt% or lower, about 2.75 wt% or lower, about 2.5 wt% or lower, about 2.25 wt% or lower, about 2 wt% or lower, or about 1.75 wt% or lower. Conductivity modifiers within this content range can improve the polishing efficiency of silicon nitride and silicon dioxide, maintaining a polishing rate selectivity ratio of silicon nitride to silicon dioxide close to 1:1; at the same time, they will not significantly affect the polishing behavior of polycrystalline silicon, protecting the polycrystalline silicon functional layer from over-polishing, thinning, or interface damage.
[0064] To further effectively suppress the grinding of polycrystalline silicon, preferably, the conductivity modifier is selected from one or more of ammonium sulfate, ammonium lactate, ammonium oxalate, ammonium succinate, and ammonium nitrate.
[0065] In this application, the chemical mechanical polishing composition may also include additives commonly used in the art, such as pH adjusters, oxidants, bactericides, etc.
[0066] The chemical mechanical polishing composition of this application can be diluted with an appropriate amount of water before use. For example, the concentration ratio of the polishing composition before and after dilution is 3:1, and the mass ratio of the polishing composition to water before dilution is 1:2.
[0067] Thirdly, this application further provides a chemical mechanical polishing method, comprising: (i) contacting a substrate with a chemical mechanical polishing composition according to any embodiment of the first aspect; (ii) moving the chemical mechanical polishing composition relative to the substrate; and (iii) polishing the substrate by removing at least a portion of the substrate; wherein the substrate comprises at least a silicon nitride layer and a silicon oxide layer, the ratio of the removal rates of the silicon nitride layer and the silicon oxide layer being 0.95 to 1.10.
[0068] Although the chemical mechanical polishing composition of this application can be used to polish any substrate (e.g., integrated circuits, metals, ILD layers, semiconductors, and thin films), it is particularly suitable for polishing substrates containing silicon nitride and silicon oxide layers.
[0069] Example
[0070] The technical solution of this application will be further described below with reference to specific embodiments.
[0071] In the examples and comparative examples, the physical properties of the chemical mechanical polishing compositions were determined according to the following methods.
[0072] (1) Specific polishing conditions: The test machine was Ebara; the polishing fluid flow rate was 220 mL / min; the dilution ratio was 1:3; the polishing pad was DH5210 (produced by Hubei Dinghui Microelectronics Materials Co., Ltd.), the dressing disk was DK3701 (Dinglong Huida), the headdown force was 2.5 psi, and the head & platen RPM was 93 / 87; the wafers used were Poly Blank wafer Thickness 5 KÅ, SiN Blank wafer Thickness 5.9 KÅ, and OX Blank wafer Thickness 7.5 KÅ.
[0073] (2) Polishing rate: The difference in film thickness before and after polishing for 1 minute is the polishing rate. The film thickness is measured using a four-probe resistivity tester.
[0074] (3) Surface defects: The number of defects in 0.04μm of OX wafer was tested using SP7.
[0075] (4) Contact angle on poly: At room temperature, the poly wafer was first acid-washed with 0.5% HF for 15 min, then rinsed with deionized water and dried; the contact angle was measured using the seat drop method, with a 1wt% aqueous solution of polysilicon polishing inhibitor as the sample. 2.67 μL of sample was squeezed each time, and the squeezed droplet was suspended at the tip of the needle; the droplet spread on the wafer surface. After the contact angle of the droplet on the wafer surface stabilized, the data was recorded; each sample was measured 6 times and the average value was taken.
[0076] (5) Conductivity: The conductivity of the polishing composition was measured using a standard conductivity meter.
[0077] Preparation Example
[0078] Take 200 mL of a 20 wt% colloidal silica dispersion (commercially available colloidal silica, such as that from Fuso) into a 500 mL beaker, add 100 mL of deionized water, and stir until homogeneous to obtain a diluted colloidal silica dispersion. Adjust the pH to 4.5–5.0, heat to 50 °C, and stir at this temperature for 30 min. Weigh 4.2 g of (3-mercaptopropyl)trimethoxysilane and add 10 mL of anhydrous ethanol to obtain a diluted solution. Slowly add this diluted solution dropwise to the pretreated colloidal silica dispersion using a pipette, stir at 50 °C for 4 h, then slowly add 30 wt% hydrogen peroxide solution, and stir at this temperature for 2 h to obtain sulfonic acid-modified silica particles.
[0079] Example 1
[0080] In this embodiment, the following components are mixed to prepare a chemical mechanical polishing composition, the specific formulation of which is as follows:
[0081] Example 1-1: Abrasive particle selection: sulfonic acid modified silica particles, average particle size 90 nm, 16 wt%; silicon nitride abrasive accelerator selection: vinyl sulfonic acid 0.05 wt%; polycrystalline silicon abrasive inhibitor selection: hydroxyethyl cellulose 0.05 wt%; conductivity regulator selection: ammonium lactate 0.5 wt%. The pH of the concentrate was adjusted to 4.3 using nitric acid and potassium hydroxide. An appropriate amount of water was added to the forward polishing composition, with a mass ratio of polishing composition to water of 1:2, to obtain a chemical mechanical polishing composition. The pH of the composition became 4.9, and the zeta potential of the sulfonic acid modified silica particles was -30 mV.
[0082] Examples 1-2 to 1-10 and Comparative Examples 1-1 to 1-5 are the same as Example 1-1 except for the type and content of the polysilicon polishing inhibitor. The contact angle of the silicon nitride polishing promoter on the polysilicon was evaluated, as were the removal rates of polysilicon (poly RR), silicon oxide (OX RR), silicon nitride (SiN RR), and the selectivity of silicon nitride to silicon oxide (SiN:OX). Specific data are shown in Table 1.
[0083] Table 1. Formulations and evaluation results of Examples 1-1 to 1-10 and Comparative Examples 1-1 to 1-5.
[0084]
[0085] Table 1 shows that the type and molecular weight of polysilicon polishing inhibitors both affect their contact angle on polysilicon wafers. When the contact angle of the polysilicon polishing inhibitor on the polysilicon wafer is less than 60°, the removal rate of polysilicon is high, which may lead to excessive removal of the polysilicon gate and affect chip performance. When the contact angle of the polysilicon polishing inhibitor on the polysilicon wafer is greater than 75°, the polysilicon polishing inhibitor also affects the removal rate of silicon oxide and silicon nitride, making it difficult to maintain high polishing efficiency and control the polishing rate selection ratio of silicon nitride to silicon dioxide to be approximately 1:1.
[0086] Example 2
[0087] In this embodiment, the following components are mixed to prepare a chemical mechanical polishing composition, the specific formulation of which is as follows:
[0088] Example 2-1: Abrasive particle selection: sulfonic acid modified silica particles, average particle size 90 nm, 16 wt%; silicon nitride abrasive accelerator selection: vinyl sulfonic acid 0.01 wt%; polycrystalline silicon abrasive inhibitor selection: hydroxyethyl cellulose 0.1 wt%; conductivity regulator selection: ammonium lactate 1.0 wt%. The pH of the concentrate was adjusted to 4.3 using nitric acid and potassium hydroxide. An appropriate amount of water was added to the forward polishing composition, with a mass ratio of polishing composition to water of 1:2, to obtain a chemical mechanical polishing composition. The pH of the composition became 4.9, and the zeta potential of the sulfonic acid modified silica particles was -30 mV.
[0089] Examples 2-2 to 2-7 and Comparative Examples 2-1 to 2-3 are identical to Example 2-1 except for the type and content of the silicon nitride polishing accelerator. The removal rate of silicon oxide (OX RR), the removal rate of silicon nitride (SiN RR), and the selectivity ratio of silicon nitride to silicon oxide (SiN:OX) were evaluated to assess the surface defects of silicon oxide. Specific data are shown in Table 2.
[0090] Table 2. Formulations and evaluation results of Examples 2-1 to 2-7 and Comparative Examples 2-1 to 2-3.
[0091]
[0092] Example 3
[0093] In this embodiment, the following components are mixed to prepare a chemical mechanical polishing composition, the specific formulation of which is as follows:
[0094] Example 3-1: Abrasive particle selection: sulfonic acid modified silica particles, average particle size 90 nm, 5 wt%; silicon nitride abrasive accelerator selection: vinyl sulfonic acid 0.02 wt%; polycrystalline silicon abrasive inhibitor selection: hydroxyethyl cellulose 0.1 wt%; conductivity regulator selection: ammonium lactate 1.5 wt%. The pH of the concentrate was adjusted to 4.3 using nitric acid and potassium hydroxide. An appropriate amount of water was added to the forward polishing composition, with a mass ratio of polishing composition to water of 1:2, to obtain a chemical mechanical polishing composition. The pH of the composition became 4.9, and the zeta potential of the sulfonic acid modified silica particles was -30 mV.
[0095] Examples 3-2 to 3-8 are identical to Example 3-1 except for the content of silica particles and silicon nitride polishing accelerator. The removal rates of silica (OX RR), silicon nitride (SiN RR), and the selectivity of silicon nitride to silica (SiN:OX) were evaluated. Specific data are shown in Table 3.
[0096] Table 3. Formulations and evaluation results of Examples 3-1 to 3-8
[0097]
[0098] Example 4
[0099] In this embodiment, the following components are mixed to prepare a chemical mechanical polishing composition, the specific formulation of which is as follows:
[0100] Example 4-1: Abrasive particle selection: sulfonic acid modified silica particles, average particle size 90 nm, 16 wt%; silicon nitride abrasive accelerator selection: vinyl sulfonic acid 0.05 wt%; polycrystalline silicon abrasive inhibitor selection: hydroxyethyl cellulose 0.1 wt%; conductivity regulator selection: ammonium lactate 0.5 wt%. The pH of the concentrate was adjusted to 4.3 using nitric acid and potassium hydroxide. An appropriate amount of water was added to the forward polishing composition, with a mass ratio of polishing composition to water of 1:2, to obtain a chemical mechanical polishing composition. The pH of the composition became 4.9, and the zeta potential of the sulfonic acid modified silica particles was -30 mV.
[0101] Examples 4-2 to 4-10 are identical to Example 4-1 except for the type and content of the conductivity modifier. The conductivity of the composition, the removal rate of polysilicon (poly RR), the removal rate of silicon oxide (OX RR), the removal rate of silicon nitride (SiN RR), and the selectivity ratio of silicon nitride to silicon oxide (SiN:OX) were evaluated. Specific data are shown in Table 4.
[0102] Table 4. Formulations and evaluation results of Examples 4-1 to 4-10
[0103]
[0104] Although the embodiments of this application have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for this application. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, this application is not limited to the specific details and embodiments shown and described herein.
Claims
1. A chemical mechanical polishing composition, characterized in that, include: Colloidal silica particles, wherein the colloidal silica particles are anion-modified, the anion being sulfonate, and the content of the colloidal silica particles is 5-20 wt%. A silicon nitride polishing accelerator, wherein the content of the silicon nitride polishing accelerator is 0.01~0.1wt%; A polycrystalline silicon polishing inhibitor, wherein a 1 wt% aqueous solution of the polycrystalline silicon polishing inhibitor has a contact angle of 60~75° on a polycrystalline silicon wafer cleaned with HF at room temperature, and the content of the polycrystalline silicon polishing inhibitor is 0.01~1 wt%. The chemical mechanical polishing composition has a pH value of 4-6. The polycrystalline silicon abrasion inhibitor is selected from one or more of hydroxymethyl cellulose, hydroxyethyl cellulose, polypropylene glycol, dextran, and hydroxypropyl cellulose. The mass ratio of the silicon nitride abrasion accelerator to the colloidal silica particles is 1:(500-600). The silicon nitride abrasion accelerator is selected from one or more of acrylic acid, methacrylic acid, ethylacrylic acid, propylacrylic acid, butylacrylic acid, crotonic acid, isocrotonic acid, maleic acid, trans-butenedioic acid, itaconic acid, citraconic acid, mesoconic acid, pentenoic acid, hexenoic acid, octenoic acid, vinyl sulfonic acid, methacrylic acid, butenyl sulfonic acid, pentenyl sulfonic acid, hexenyl sulfonic acid, and styrene sulfonic acid. The electrical conductivity of the composition is 0.5-3 mS / cm.
2. The chemical mechanical polishing composition according to claim 1, characterized in that, The silicon nitride polishing accelerator is selected from one or more of vinyl sulfonic acid and styrene sulfonic acid.
3. The chemical mechanical polishing composition according to any one of claims 1 or 2, characterized in that, The colloidal silica particles have an average primary particle size range of 30~150nm, exhibit negative charge in the polishing composition, and have a surface zeta potential of less than -20mV.
4. The chemical mechanical polishing composition according to claim 3, characterized in that, The anion is selected from one or more of methanesulfonic acid group and propanesulfonic acid group.
5. The chemical mechanical polishing composition according to any one of claims 1 or 2, characterized in that, The composition further includes a conductivity modifier, which is an ammonium salt, and the content of the conductivity modifier is 0.5~3wt%.
6. The chemical mechanical polishing composition according to claim 5, characterized in that... The conductivity modifier is selected from one or more of ammonium sulfate, ammonium lactate, ammonium oxalate, ammonium succinate, and ammonium nitrate.
7. A chemical mechanical polishing method, characterized in that, include: (i) Using a substrate to contact the chemical mechanical polishing composition according to any one of claims 1 to 6; (ii) Moving the chemical mechanical polishing composition relative to the substrate; and (iii) Grinding away at least a portion of the substrate to polish the substrate; The substrate comprises at least one silicon nitride layer and one silicon oxide layer, wherein the ratio of the removal rates of the silicon nitride layer and the silicon oxide layer is 0.95 to 1.10.
Citation Information
Patent Citations
Polishing agent for silicon oxide, liquid additive, and method of polishing
CN102965025A
Chemical mechanical polishing composition for silicon nitride layer
KR1020090035063A
Polishing composition, polishing method, and method of manufacturing semiconductor substrate
US20250109318A1
KR20240128578A